Pengembangan Buku Cerita Interaktif sebagai Media Edukasi untuk Mengenalkan Identitas Gender pada Anak Usia Dini - Aina Zillan Zalila; Hikmah Hikmah; Ajeng Fitri Untariana (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to develop interactive storybooks as educational media to introduce gender identity in early childhood. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were children aged 5-6 years at BKB PAUD Mulia and TK Bahtera Ceria, selected through purposive sampling. Data were collected through observation, interviews, questionnaires, and expert validation, and analyzed using quantitative and qualitative descriptive techniques. The results showed that material expert validation reached 89.06% and media expert validation reached 85%, categorized as highly feasible. Educational practitioners’ assessment reached 99.04%, parents’ responses reached 87.56%, and children’s observations showed highly positive responses. The media effectively helped children understand self-identity, gender identity, and body safety in a more concrete way. Therefore, the interactive storybooks are feasible as educational media for early childhood. Further studies are recommended to conduct broader and longer-term implementation.